Criminological Review of Domestic Violence Against Wife: Case Study of Boalemo Police Station - Bakue, Risma; Pade, Sri Rahayu Lestari; Z. Mamu, Karlin; Ekwanto, Endah Rizki (IJBLE Scientific Publications Community Inc., 2024)
ABSTRACT Domestic violence is a serious problem that needs to be dealt with firmly, because acts of violence committed by husbands against wives result in physical, sexual, psychological, and even death. This study aims to determine the factors that cause domestic violence against wives and police efforts in reducing / overcoming criminal acts of domestic violence against wives. This research uses empirical research methods, by analyzing data obtained from the object of research and conducting interviews. Based on the results of this study, it shows that the factors that cause domestic violence against wives are infidelity factors, economic factors, alcoholic beverage factors and police efforts in reducing / overcoming criminal acts of domestic violence against wives are carried out by preventive efforts, namely socialization related to the Law on the Elimination of Domestic Violence, conducting coaching, and repressive efforts, namely taking action.